Pengembangan Kreativitas Anak Asuh melalui Handycraft Panti Asuhan Al-Amin Geluran Taman Sidoarjo - Budi Purwantiningsih; M. Rasikhul Islam (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2017)
Foster parents play an important role to explore and develop the potential of foster children's creativity. Therefore the purpose of this research is 1) The opening of knowledge of children al-Amin in making handycraft. 2) The establishment of a sense of motivational development of children al-Amin to optimize the manufacture of handycraft. 3) The establishment of a sense of belonging (self belonging) childrenOrphanage al-Amin to handycraft business results. 4) The creation of a sense of professionalism students in developing this handycraft business so it is expected to be a provision of business and provision of life later than al-Amin orphanage. This research is a descriptive research. Companion is instrumental in providing motivation to children, as well as directing the activities of foster children to be useful in the future. One of them is to motivate and lead the children to participate in creative development activities in the form of handycrafts. Forms of activities undertaken by children in the form of handycraft of ribbons, beads and patchwork that can be used for sale freely or wedding souvenirs